KETIDAKADILAN GENDER DALAM NOVEL PEREMPUAN BERKALUNG SORBAN KARYA ABIDAH EL KHALIEQY SERTA NILAI PENDIDIKAN KARAKTERNYA - Tri Budi Astuti; Lulus Irawati; Dwi Rohman Soleh (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
This study aims to describe: (1) the form of gender injustice experienced by Javanese women in the novel Perempuan Berkalung Sorban (2) the value of character education contained in the novel Perempuan Berkalung Sorban. This research is a descriptive qualitative research with literary feminism approach. The data source in this study is a document in the form of the novel Perempuan Berkalung Sorban by Abidah El Khalieqy. The data collection of this research includes reading, recording, and analyzing documents. The data analysis technique used in this study is a content analysis technique which includes data reduction, data presentation, and data inference. The results of this study (1) the forms of gender injustice against female figures are subordination, stereotypes, violence and double work. (2) the value of character education that appears in the novel Perempuan Berkalung Sorban is religious, hard work, democratic, curious, fond of reading, and social care